Novel continuous up-flow MFC for treatment of produced water: Flow rate effect, microbial community, and flow simulation. (February 2022) - Cabrera, Jonnathan; Dai, Yexin; Irfan, Muhammad; Li, Yang; Gallo, Felix; Zhang, Pingping; Zong, Yanping; Liu, Xianhua
Abstract: Produced water (PW) is the main waste produced by oil and gas industry, and its treatment represents an environmental and economical challenge for governments and the industry itself. Microbial fuel cells (MFC) emerge as an ecofriendly technology able to harvest energy and remove pollutants at the same time, however high internal resistance is a key problem limiting their operating performance and practical application. In this work, a novel continuous up-flow MFC was designed and fed solely using PW under different flowrates. Effects of the different flowrates (0 mL/s, 0.2 mL/s, 0.4 mL/s, and 0.6 mL/s) in power production performance and pollutants removal were analyzed. Our results demonstrated the removal efficiency of all the pollutants improved when flowrate incremented from 0 to 0.4 mL/s (COD: 96%, TDS: 22%, sulfates: 64%, TPH: 89%), but decreased when 0.6 mL/s was applied. The best power density of 227 mW/m 2 was achieved in a flowrate of 0.4 mL/s. Similar to the pollutant's removal, the power density increased together with the increment of flowrate and decreased when 0.6 mL/s was used. The reason for the performance fluctuation was the decrement of internal resistance from 80 Ω (batch mode) to 20 Ω (0.4 mL/s), and then the sudden increment to 90 Ω for 0.6 mL/s. A flow simulation revealed that until 0.4 mL/s the flow was organized and helped protons to arrive in the membrane faster, but flowrate of 0.6 mL/s created turbulence which prejudiced the transportation of protons incrementing the internal resistance. Microbial community analysis of the biofilm found that Desulfuromonas, Desulfovibrio and Geoalkalibacter were dominant bacteria in charge of pollutant removal and electricity production. This study can be helpful in guiding the use of continuous-flow MFC for PW treatment, and to accelerate the practical application of MFC technology in oil industry. Graphical abstract: Image 1 Highlights: A novel continuous up-flow MFC was designed and used for the first time to treat PW. Increment of flowrate improved MFC performance but excessive increment worsened it. Microbial analysis suggested that sulfates are the main TEA for PW treatment in MFC. Improvement of power density was linked to the decrement of internal resistance. This study is helpful in guiding the use of continuous-flow MFC for PW treatment.